2006
DOI: 10.2175/106143005x84521
|View full text |Cite
|
Sign up to set email alerts
|

The Digestibility of Waste Activated Sludges

Abstract: Laboratory digestion studies using waste activated sludges (WAS) were conducted to compare the digestion performance between anaerobic and aerobic processes. Nine samples of WAS from seven wastewater treatment plants were collected and batch‐digested under both anaerobic and aerobic conditions for 30 days at 25 °C. The cation content of wastewater (both floc and solution phases) and solution biopolymer (protein and polysaccharide) was measured before and after digestion and compared with volatile solids destru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 21 publications
7
45
1
Order By: Relevance
“…It is not known whether such mechanism is of importance during WP. The calcium concentrations remain in sharp contrast to what other authors found with regard to the release of soluble Ca 2+ [66,68]. A possible explanation for the relatively stable Ca 2+ concentrations, when comparing WAS and ER, is the difference in batch duration, which was 30 days in the aforementioned studies versus 4 days in our present study.…”
Section: Total and Dissolved Cationscontrasting
confidence: 97%
See 4 more Smart Citations
“…It is not known whether such mechanism is of importance during WP. The calcium concentrations remain in sharp contrast to what other authors found with regard to the release of soluble Ca 2+ [66,68]. A possible explanation for the relatively stable Ca 2+ concentrations, when comparing WAS and ER, is the difference in batch duration, which was 30 days in the aforementioned studies versus 4 days in our present study.…”
Section: Total and Dissolved Cationscontrasting
confidence: 97%
“…A similar trend was observed for humic-like substances. The release of soluble carbohydrates and proteins, upon aerobic treatment of WAS, has been reported also by other authors [66,68]. Results are from a 3-day batch experiment with VS reduction of 63% ± 3 and 13% ± 3 for WP and ER, respectively, using a worm/VS ratio of 15 g/g.…”
Section: Soluble Codsupporting
confidence: 67%
See 3 more Smart Citations